Tinjauan Yuridis Pasal 75 Undang-Undang Keimigrasian Terhadap Pengawasan Orang Asing Dalam Ekosistem Ekonomi Digital Indonesia - I Gede Prama Dutha Eswara; I Made Rico Dvipayana; Faizh Ramadhani (Universitas Medan Area, 2026)
This study aims to determine and analyze the immigration oversight system, which still relies on Article 75 of Law Number 6 of 2011, which contains multi-interpretable phrases such as